Mechanizm nabytej apraksji mowy i sposoby jej diagnozowania - Rutkiewicz-Hanczewska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(--scale-factor)*65.77px); top: calc(var(--scale-factor)*482.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.981485);" role="presentation">The subject of this article is the specificity <span dir="ltr" style="left: calc(var(--scale-factor)*234.60px); top: calc(var(--scale-factor)*482.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.996562);" role="presentation">of acquired apraxia of speech and the inclu<span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*496.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0114);" role="presentation">sion <span dir="ltr" style="left: calc(var(--scale-factor)*85.33px); top: calc(var(--scale-factor)*496.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.99222);" role="presentation">and exclusion <span dir="ltr" style="left: calc(var(--scale-factor)*142.19px); top: calc(var(--scale-factor)*496.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.986012);" role="presentation">criteria for diagnosing this type of disorder. The article draws atten<span dir="ltr" style="left: calc(var(--scale-factor)*66.32px); top: calc(var(--scale-factor)*510.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03985);" role="presentation">tion <span dir="ltr" style="left: calc(var(--scale-factor)*84.38px); top: calc(var(--scale-factor)*510.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02185);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*94.21px); top: calc(var(--scale-factor)*510.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01264);" role="presentation">the distinction <span dir="ltr" style="left: calc(var(--scale-factor)*153.76px); top: calc(var(--scale-factor)*510.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988685);" role="presentation">between apraxia of speech and aphasia or dysarthria with which<span dir="ltr" style="left: calc(var(--scale-factor)*66.29px); top: calc(var(--scale-factor)*524.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.96571);" role="presentation"> it very often coexists. It describes the process of diagnosing it, which should include the<span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*538.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.998998);" role="presentation"> assessment of the consistency of an utterance, its accuracy and fluency, and therefore<span dir="ltr" style="left: calc(var(--scale-factor)*66.32px); top: calc(var(--scale-factor)*552.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.984806);" role="presentation"> the degree of adequacy of repeated statements, differentiation <span dir="ltr" style="left: calc(var(--scale-factor)*310.93px); top: calc(var(--scale-factor)*552.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0058);" role="presentation">of errors (phonetic, pho<span dir="ltr" style="left: calc(var(--scale-factor)*66.30px); top: calc(var(--scale-factor)*566.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.967463);" role="presentation">nological) that accompany it, and speech fluency. The article also discusses the tools for <span dir="ltr" style="left: calc(var(--scale-factor)*66.45px); top: calc(var(--scale-factor)*580.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.998846);" role="presentation">studying apraxia of speech currently existing worldwide, including hierarchical word<span dir="ltr" style="left: calc(var(--scale-factor)*66.28px); top: calc(var(--scale-factor)*594.50px); font-size: calc(var(--scale-factor)*10.00px); font-family: serif; transform: scaleX(0.979169);" role="presentation"> lists and scales for its assessment.